Optimalisasi Modal Sosial Keluarga Muda dalam Membangun Ketahanan Ekonomi di Era Covid-19: Studi Kasus di Perdesaan Jawa - Setiadi Setiadi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2020)
The Covid-19 pandemic has caused acute non-health impacts for various levels of society, including young families in rural areas of Java. This study presents the results of research that focus on the experiences of young families who work in the informal sector in overcoming the economic impacts due to the Covid-19 pandemic. The young families in this study were those who got married less than 10 years and/or had the oldest child aged less than 10 years. By using an anthropological approach and applying data collection method through participatory observations and in-depth interviews, this study concluded that there were two factors that made them be the most vulnerable group, yet they could face economic emergencies at the same time, such as first, their ability to optimize social capital to increase their own capacity and their family’s capacity in the face of economic vulnerability. They did productive economic activities by optimizing very limited work networks to survive their life. Second, they carefully performed minimal income management so that they could survive and fulfill the minimum household needs as a household unit.